Pelatihan Olah Sayur Hasil Kebun: Pembuatan Es Krim Berbasis Sayuran Di PT Great Giant Food, Terbanggi Besar, Lampung Tengah - Elly Lestari Rustiati; Susilawati; Agus Subagyo; Putri Dwi Astuti; Fauzan Khumaidi; Dewi Puspita Widiarini (CV. Multi Kreasi Media, 2025)
A training program on processing local vegetables into vegetable-based ice cream was conducted at PT Great Giant Food (GGF), Central Lampung, aimed at empowering women's groups to enhance the value of local agricultural products. The training involved 32 participants from the GGF Employees' Wives Association and the Tulip Women Farmers Group. Activities included nutrition education, demonstrations, product tasting, and hands-on practice in making ice cream using pakcoy and bokcoy. A participatory and practical approach encouraged active engagement, improved technical skills, and fostered flavor innovation. The results showed that participants successfully produced vegetable ice cream with favorable organoleptic qualities. This initiative not only promoted local resource utilization but also strengthened women's economic roles and aligned with sustainable development goals. The training model presents strong potential for replication in similar community contexts.